2022
DOI: 10.1186/s12969-022-00663-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term growth and final adult height outcome in childhood-onset systemic lupus erythematosus

Abstract: Background Growth impairment is the most common complication in patients with childhood-onset systemic lupus erythematosus (cSLE). There are limited data on risk factors affecting growth development in Asian patients with cSLE. This study aimed to determine the predictors of growth impairment in such patients. Methods All SLE patients aged < 15 years diagnosed in Ramathibodi Hospital between 2006 and 2016 were enrolled in a retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Female patients who developed SLE before menarche are shorter than those who developed SLE after menarche ( Sontichai et al, 2022 ). Research focusing on children with SLE has also identified sex and hormone use as factors that lead to reduced final height in patients with SLE ( Jongvilaikasem and Rianthavorn, 2021 ; Ponin et al, 2022 ). A study on bone remodeling in children and youths with SLE showed that the dose of glucocorticoids was a negative predictor of bone formation, whereas SLE disease activity was unrelated to bone formation ( Baker-LePain et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Female patients who developed SLE before menarche are shorter than those who developed SLE after menarche ( Sontichai et al, 2022 ). Research focusing on children with SLE has also identified sex and hormone use as factors that lead to reduced final height in patients with SLE ( Jongvilaikasem and Rianthavorn, 2021 ; Ponin et al, 2022 ). A study on bone remodeling in children and youths with SLE showed that the dose of glucocorticoids was a negative predictor of bone formation, whereas SLE disease activity was unrelated to bone formation ( Baker-LePain et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Premature menarche has been considered a risk factor for the development of SLE, 5 while the development of SLE prior to menarche may delay menarche in patients. 6,7 In contrast, a later AAM has been observed to reduce the risk of SLE in black women, and SLE patients may experience a later menarche than healthy controls. 8 Furthermore, pregnancy in patients with SLE is usually associated with greater risk, as pregnancy itself often causes recurrences of SLE.…”
Section: Introductionmentioning
confidence: 99%